FAKTOR FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN PROPERTI - Januri, Januri (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The high income tax expense causes the company to carry out earnings management. Decreased earnings management tends to result in high tax planning. The company's ability to pay off short-term liabilities by using good current assets (current ratio) will reduce earnings management practices. This study aims to test and analyze how much influence the income tax expense has on earnings management, test and analyze how much influence tax planning has on earnings management, and to test and analyze how much influence the current ratio has on earnings management. This type of research is quantitative by using the sampling technique is purposive sampling. To collect sample data, researchers used secondary data, namely documentation on the Indonesia Stock Exchange (BEI). To process the data obtained, the researchers used SSS as a data analysis tool. Based on the results of the study, it can be concluded that the variable income tax expense, tax planning and current ratio simultaneously do not have a significant effect on earnings management. So it can be concluded that income tax expense (X1), tax planning (X2) and current ratio (X3) do not simultaneously affect earnings management (Y) in property companies listed on the Indonesia Stock Exchange (BEI).